The Scales of the European Court of Human Rights: Abortion Restriction in Poland, the European Consensus, and the State's Margin of Appreciation - Julia Kapelańska-Pręgowska (Harvard FXB Center for Health and Human Rights, 2020)
In October 2020, the Polish Constitutional Court held unconstitutional an exception in the Family Planning Act of 1993 that provided for legal abortion in cases of fetal abnormalities. This retrogressive step has led to an almost total ban on abortion in Poland. Drawing on existing Strasbourg case law and other relevant legal material, this paper attempts to anticipate a possible outcome of applications recently filed before the European Court of Human Rights by more than 1,000 Polish women who were denied abortions or who postponed their reproductive decisions out of fear. I focus on two factors that play a determining role in the adjudication of cases related to reproductive rights. The first one is a public interest in restricting abortion-namely, the "protection of morals." The second is the margin of appreciation doctrine, which determines the degree of freedom that states enjoy in regulating certain issues, such as abortion, and which is highly dependent on the concept of a European consensus. I argue that this consensus-revealed through the domestic laws and practice of 47 Council of Europe member states-shows considerable unity and should thus restrict individual states' discretion in limiting human rights and freedoms. The European Court of Human Rights, by acknowledging the relevance of a European consensus in abortion regulation, as well as evolving universal standards concerning reproductive rights, would avoid two pitfalls: one connected with analyzing the doubtful public interest in protecting morals, and another with a potential criticism of judicial activism and the court's imposition of its own moral evaluation of an abortion ban.